2018
DOI: 10.1016/j.jpha.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Novel ligand-based docking; molecular dynamic simulations; and absorption, distribution, metabolism, and excretion approach to analyzing potential acetylcholinesterase inhibitors for Alzheimer's disease

Abstract: Acetylcholinesterase (AChE) plays an important role in Alzheimer's disease (AD). The excessive activity of AChE causes various neuronal problems, particularly dementia and neuronal cell deaths. Generally, anti-AChE drugs induce some serious neuronal side effects in humans. Therefore, this study sought to identify alternative drug molecules from natural products with fewer side effects than those of conventional drugs for treating AD. To achieve this, we developed computational methods for predicting drug and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 30 publications
1
28
0
2
Order By: Relevance
“…In previous works of Szwajgier [26,27], quercetin and kaempferol were efficient AChE and BChE inhibitors, whereas the activity of rutin was considerably lower in comparison to its aglycone [26,28]. Efficient inhibition of AChE, BChE, or both by quercetin [29,30] as well as rutin was also confirmed by other authors [29,31,32]. Additionally, other authors demonstrated anti-AChE activity of quercetin in vivo in the brain tissue of zebrafish in AD models [33,34].…”
Section: Discussionsupporting
confidence: 53%
“…In previous works of Szwajgier [26,27], quercetin and kaempferol were efficient AChE and BChE inhibitors, whereas the activity of rutin was considerably lower in comparison to its aglycone [26,28]. Efficient inhibition of AChE, BChE, or both by quercetin [29,30] as well as rutin was also confirmed by other authors [29,31,32]. Additionally, other authors demonstrated anti-AChE activity of quercetin in vivo in the brain tissue of zebrafish in AD models [33,34].…”
Section: Discussionsupporting
confidence: 53%
“…Molecular docking approach identifies suitable drug molecules for the target of interest (Roy et al., 2015 ; Sharma et al., 2011 ; Subhani et al., 2015 ; Vijayakumar et al., 2018 ). The docking result shows the potential of Dex to bind within the receptor pockets or active sites ( Figure 2 ) and the hydrogen bond interactions within specified distances ( Figures 3 and 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Counter ions were added to the complex to neutralize the solvated system. The complex energy was minimized using an OPLS3e force field [ 26 , 27 ]. In the current study, isothermal-isobaric (NPT) ensemble was employed.…”
Section: Methodsmentioning
confidence: 99%